FACILITATING DESIGN FOR ASSEMBLY THROUGH THE ADOPTION OF A PROACTIVE DESIGN METHODOLOGY - Desai, Anoop Arun; Mital, Anil (International Journal of Industrial Engineering: Theory, Applications and Practice, 2010)
The principal objective of this paper is to present a comprehensive Design for Assembly methodology. This will enable product designers of both simple as well as complex products and systems to proactively design for ease of assembly. A product/system that is easy to assemble tends to lend itself to expedited manufacturing cycle times by means of reducing the time required during product assembly. Similarly, the methodology also makes special concessions for incorporating ‘green techniques’ during the assembly process. This is especially important given the current emphasis being placed on ‘green’ design and environment conscious manufacturing. This paper is divided into two parts. The first part presents a brief overview of some commonly used practices that focus on design for assembly. The second part presents the aforementioned methodology. The methodology is corroborated by means of a real life case study that proves its practical usefulness.